The Long Sixth Century in Eastern Europe - Curta, Florin, author.
1 online resource.
Keywords: In The Long Sixth Century in Eastern Europe , Florin Curta offers a social and economic history of East Central, South-Eastern and Eastern Europe during the 6th and 7th centuries. It challenges the current model of transition from Antiquity to the early Middle Ages on the basis of an interpretation of the written sources, but especially of an enormous amount of archaeological evidence accumulated in the last 50 years or so. It deals with societies in close contact with the Roman world, as well with those located very far from it. It addresses questions of property, subsistence, crafts, trade, and social change.